International Students’ Perceptions of the Value of U.S. Higher Education - Urban, Ewa; Palmer, Louann Bierlein (Journal of International Students, 2016)
We examined international students’ perceptions of the personal and professional value they receive from higher education in the United States. Results indicated that students’ professional outcomes were significantly lower than their expectations related to their professional development, while students benefited personally to a much greater extent than they had anticipated. In this study, we identified areas of opportunities for higher education to support international students’ professional and personal goals.